2019
DOI: 10.1021/acssuschemeng.9b05400
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase Immobilization onto Magnetic Halloysite Nanotubes: Enhanced Enzyme Activity and Stability with High Cellulose Saccharification

Abstract: A quest for efficient biotransformation of cellulosic material into sustainable biochemical products for recent biotechnological interventions is currently under way. Herein, we report the fabrication of nanobiocatalyst (NBC) employing halloysite nanotubes (HNTs) as a template for immobilizing cellulase enzyme, which catalyzed the hydrolysis of cellulose into glucose. Magnetic character was imported to HNTs by in situ anchoring of iron oxide nanoparticles, onto which cellulase was immobilized using aminosilane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 52 publications
5
48
0
Order By: Relevance
“…More sophisticated approaches to enzyme retention have been investigated by immobilizing the enzyme on specific supports such as nanofibers, nanoparticles and organic metal frames. Sillu et al [64] proposed the immobilization of cellulase on magnetic halloysite nanotubes. Driven by the potential ease of the recovery, the use of magnetic CLEA (Cross Linked Enzyme Aggregates) of cellulase for the hydrolysis of cellulose has been successfully reported at lab scale by several contributions [65][66][67].…”
Section: Bioreactor Designmentioning
confidence: 99%
“…More sophisticated approaches to enzyme retention have been investigated by immobilizing the enzyme on specific supports such as nanofibers, nanoparticles and organic metal frames. Sillu et al [64] proposed the immobilization of cellulase on magnetic halloysite nanotubes. Driven by the potential ease of the recovery, the use of magnetic CLEA (Cross Linked Enzyme Aggregates) of cellulase for the hydrolysis of cellulose has been successfully reported at lab scale by several contributions [65][66][67].…”
Section: Bioreactor Designmentioning
confidence: 99%
“…Sillu & Agnihotri [37] developed magnetic halloysite nanotubes (MHNTs), a different conformation consisting of silica-based nanotubes of Al 2 SiO 5 (OH) 4 .2H 2 O that present silanol (-Si-OH) and siloxane groups (-Si-O-Si-) at the surface. The first step was the coating of MNPs in situ with halloysite nanotubes; then, it was grafted with amino groups using 3-APTES and activated, resulting in protein loading of 80.48% and cellulase activity yield of about 93.5%.…”
Section: Immobilization and Co-immobilization Of Cellulose-degrading Enzymes Using Silica-based Carriersmentioning
confidence: 99%
“…It is essential to note that the optimization step is fundamental for immobilized enzyme efficiency, catalytic activity, stability, and recycling ability. The studies that previously determined the optimal immobilization parameters have usually shown better yields and efficiencies in enzyme immobilization [12,37,47,52,56,64,65].…”
Section: Key Factors Of Magnetic Enzyme Immobilizationmentioning
confidence: 99%
“…Similarly, in 2020 cellulase enzyme was grafted on magnetic HNTs’ (MHNTs’) external surface for biocatalytic purposes ( Figure 9 ) [ 121 ]. It was demonstrated that the nanomaterial exhibited an excellent catalytic activity at elevated temperatures, ionic liquid-tolerant characteristics, hydrolyzation continuously over longer durations, and eco-friendly attributes, features which made the cellulase-MHNTs amenable for high cellulose conversion.…”
Section: Covalent Modification Of the External Halloysite Surfacementioning
confidence: 99%
“… Schematic representation of the synthesis of cellulase-MHNTs (magnetic HNTs). Reproduced with permission from [ 121 ]. …”
Section: Figurementioning
confidence: 99%